2008
DOI: 10.1002/casp.960
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious and post‐memory practices in adopting families: The re‐production of the past through photography and narrative

Abstract: In this paper, we explore how adoptive parents manage and order visual information relating to their adoptive child's birth or foster family. More specifically, our task is to make sense of the ways in which the memories that children have of their past families are (re)constructed and managed within the context of present adoptive parental concerns. Life story books have become a dominant way in which narratives of the child's past family are formed. The aim of this book is to provide the child with relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…However, their very absence can demand attention and be effective. This need not result in lost opportunities but can encourage reflection on the absent object and on the research process (Brookfield et al 2008;Frith & Harcourt 2007;Hodgetts et al 2007b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, their very absence can demand attention and be effective. This need not result in lost opportunities but can encourage reflection on the absent object and on the research process (Brookfield et al 2008;Frith & Harcourt 2007;Hodgetts et al 2007b).…”
Section: Discussionmentioning
confidence: 97%
“…I've even asked friends to get rid of their photos of me. [Ismene] Besides destroying evidence there were also times when photographs were not taken or not kept (Brookfield, Brown & Reavey 2008;Hodgetts, Chamberlain & Radley 2007b). These lacks of materiality worked to expand the narrative as participants attempted to explain them.…”
Section: Thickening the Narrative: Things Elaborate The Storymentioning
confidence: 99%
“…A wealth of literature across the social sciences indeed documented the collective sensemaking function of storytelling, in both small and large groups. For example, research on small groups such as families suggested it is possible to re‐story problematic life events that may have disrupted shared systems of belief by narrating them together (Brookfield, Brown, & Reavey, ; Koenig Kellas & Trees, ; Monk, ). Sensemaking in family remembering is enabled by members adopting different roles.…”
Section: The Collective Sensemaking Function Of Storytellingmentioning
confidence: 99%
“…A wealth of literature across the social sciences indeed documented the collective sensemaking function of storytelling, in both small and large groups. For example, research on small groups such as families suggested it is possible to re-story problematic life events that may have disrupted shared systems of belief by narrating them together (Brookfield, Brown, & Reavey, 2008;Koenig Kellas & Trees, 2006;Monk, 1997). Sensemaking in family remembering is enabled by members adopting different roles.…”
Section: The Collective Sensemaking Function Of Storytellingmentioning
confidence: 99%